APPLICATION OF COMPREHENSIVE FUZZY EVALUATION BASED ON STUDENT PARTICIPATION IN GENERAL EDUCATION COURSE EXAMINATION - Zhao, Xuanze; Zhou, Xiaohui (International Journal of Research -GRANTHAALAYAH, 2021)
In view of the assessment methods of general education courses, an assessment and evaluation model is constructed, which consists of the usual results, material learning, cooperative discussion and classroom performance, and the final results, which are combined with on-site assessment and paper assessment. Introducing students to participate in the process assessment and on-site assessment of general education courses innovatively improves students' enthusiasm to participate in the general education class. In the process of empirical research, the order relation analysis method was firstly used to judge the importance of "homework summary, material learning, cooperative discussion, classroom performance ", etc., and then the weight coefficient was determined. Then the comprehensive evaluation method based on fuzzy mathematics was adopted. Homework summary, material learning, cooperative discussion, classroom performance review and field is not so easy to use, such as the exact scores show with the method of fuzzy evaluation, the process of fully reflect the students' learning process of a curriculum, and intensify students participate in class, let students participate in curriculum evaluation, can more active classroom and improve the effect of course.